Pengaruh Lingkungan Kerja, Semangat Kerja, dan Kompetensi Terhadap Kinerja Karyawan Pada CV Tirto Agung Motor Surabaya - Pratama, Duta Wira; Utari, Woro (Jurnal Inspirasi Ilmu Manajemen, 2025)
Employee performance at CV. Tirto Agung Motor Surabaya is influenced by the work environment, work spirit, and competence which are the main focus of this study. A total of 35 permanent employees of CV. Tirto Agung Motor Surabaya were used as respondent samples using a purposive sampling method, where the population in this study was 87 people. The t-test and F-test statistics used SPSS 27 as a data analysis tool. The results of the study showed that partially through the t-test, employee performance was positively and significantly influenced by the work environment, work spirit, and competence. Furthermore, through the F-test it was proven that the three variables simultaneously also had a positive and significant effect on employee performance.